Modification of the extension block Kirschner wire technique for mallet fractures - (:unkn) unknown (My University, 2002)
A modification of the extension block Kirschner wire technique that is used for closed reduction of mallet fractures is described. Eighteen mallet avulsion fractures of the distal phalanx treated with this modification were included in this prospective study. The fingers affected were nine small fingers, eight ring fingers, and one long finger. Surgical indications included fractures involving more than 33% of the articular surface and fractures associated with subluxation of the distal phalanx that could not be corrected by closed reduction. The average joint surface involvement was 39.8%. At followup, only one patient had pain, and that was graded as minimal. Objectively, congruous and satisfactory joint surfaces were present in 17 patients. No patient had pseudarthrosis. The average active flexion of the distal interphalangeal joint was 81.1 degrees and the average extensor lag was 1.6 degrees. Neither pin tract infections nor migration of the pins occurred. The average followup was 27.3 months. This modification increased range of motion at the distal interphalangeal joint and showed a trend toward reduced permanent extensor lag when compared with the original method. This technique should be considered when treatment of the mallet fracture is being planned using the extension block Kirschner wire technique.
Keywords: Adult; Female; Humans; Middle Aged; Male; Radiography; Range of Motion, Articular; Prospective Studies; Fracture Fixation, Internal; Finger Joint; Fractures, Bone; Bone Wires; Finger Injuries